Soil remediation using a coupled process: soil washing with surfactant followed by photo-Fenton oxidation - Villa, Ricardo D. [UNESP]; Trovo, Alam G. [UNESP]; Pupo Nogueira, Raquel F. [UNESP] (Elsevier B.V., 2010)
In the present work the use of a coupled process, soil washing and photo-Fenton oxidation, was investigated for remediation of a soil contaminated with p.p'-DDT (DDT) and p.p'-DDE (DDE), and a soil artificially contaminated with diesel. In the soil washing experiments,Triton X-100(TX-100) aqueous solutions were used at different concentrations to obtain wastewaters with different compositions. Removal efficiencies of 66% (DDT). 80% (DDE) and 100% (diesel) were achieved for three sequential washings using a TX-100 solution strength equivalent to 12 times the effective critical micelle concentration of the surfactant (12 CMC(eff)). The wastewater obtained was then treated using a solar photo-Fenton process. After 6 h irradiation, 99, 95 and 100% degradation efficiencies were achieved for DDT, DDE and diesel, respectively. In all experiments, the concentration of dissolved organic carbon decreased by at least 95%, indicating that residual concentration of contaminants and/or TX-100 in the wastewater was very low. The co-extraction of metals was also evaluated. Among the metals analyzed (Pb, Cr, Ni, Cu. Cd, Mn and Co), only Cr and Mn were detected in the wastewater at concentrations above the maximum value permitted by current Brazilian legislation. The effective removal of contaminants from soil by the TX-100 washing process, together with the high degradation efficiency of the solar photo-Fenton process, suggests that this procedure could be a useful option for soil remediation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Soil; Triton X-100; Remediation; Organochlorine; Fuels; Pesticides